2021
DOI: 10.7759/cureus.16929
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Lipoma of the Calcaneum

Abstract: Lipomas are benign lesions of adipose tissue, which commonly affect the soft tissues but are rarely found in the musculoskeletal system. Intraosseous lipomas are rare benign tumors and even rarer in calcaneum, only to be found incidentally in the majority of cases. We report a case of a 45-year-old male patient who presented to the outpatient department with complaints of bilateral heel pain, which was initially treated conservatively as the presentation was similar to plantar fasciitis. On further follow-up, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…There is also another theory stating "metaplasia theory" where these occur due to aberrant differentiation of in situ mesenchymal cells into lipoblast because, from mutable cells of connective tissue, adipose tissue can be derived in any part of the body [10,11]. Some authors also concluded that lipoma is benign, congenital arising from multipotential cells of the embryo, and remains inactive subclinically, which under hormonal influence develops into adolescence and differentiates into adipose cells [8,9,11]. In some cases, trauma and chronic irritation fasten the proliferation of soft tissue and develop a lipoma [9][10][11].…”
Section: Pathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…There is also another theory stating "metaplasia theory" where these occur due to aberrant differentiation of in situ mesenchymal cells into lipoblast because, from mutable cells of connective tissue, adipose tissue can be derived in any part of the body [10,11]. Some authors also concluded that lipoma is benign, congenital arising from multipotential cells of the embryo, and remains inactive subclinically, which under hormonal influence develops into adolescence and differentiates into adipose cells [8,9,11]. In some cases, trauma and chronic irritation fasten the proliferation of soft tissue and develop a lipoma [9][10][11].…”
Section: Pathogenesismentioning
confidence: 99%
“…Some authors also concluded that lipoma is benign, congenital arising from multipotential cells of the embryo, and remains inactive subclinically, which under hormonal influence develops into adolescence and differentiates into adipose cells [8,9,11]. In some cases, trauma and chronic irritation fasten the proliferation of soft tissue and develop a lipoma [9][10][11].…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations